Pengaruh Net Profit Margin (Npm) Dan Quick Ratio (Qr) Terhadap Harga Saham Pada PT Sumber Alfaria Trijaya Tbk Periode 2014-2023 - Dona Palintina; Andriyani Hapsari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to analyze the effect of Net Profit Margin (NPM) and Quick Ratio (QR) on the share price of PT Sumber Alfaria Trijaya Tbkfor the 2014-2023 period. This study uses a quantitative method with an associative approach. The data used is secondary data in the form of the company's annual financial statements obtained from the company's official website and the Indonesia Stock Exchange. The data analysis technique used multiple linear regression analysis with the help of the SPSS V25 program, which included classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation tests), hypothesis tests (t tests and F tests), and determination coefficient tests (R²). The results of the study show that the Net Profit Margin (NPM) variable partially NPM has a positive and very significant effect on the stock price, as evidenced by the t-test with a significance value of 0.001 < 0.05 and a t-calculation value of 6.023 > t-table of 2.365, then the decision is that H0 is rejected and Ha is accepted. Then the Quick Ratio (QR) variable partially QR does not have a significant effect on the stock price is proven by the t-test with the result of a significance value of 0.691 > 0.05 and a t-calculation value of 0.414 < t-table of 2.365. Thus, the decision is that H0 is accepted and Ha is rejected. Net Profit Margin and Quick Ratio together (simultaneously) have a significant effect on the stock price by finding if the significance value is 0.002 < 0.05 and the value of Fcal is 18.168 > of Ftable (4.74), then the result is that H0 is rejected and Ha is accepted. A determination coefficient value (R²) of 0.838 or 83.8% indicates that NPM and QR are able to explain 83.8% of stock price variations, while the remaining 16.2% are explained by other variables outside the study.